(untitled) (INNOVATIVE ECONOMY, 2020)
Valiullina Z.V. FORMATION OF INFORMATION AND INSTITUTIONAL ENVIRONMENT OF CORPORATE ACTIVITIES Purpose. The aim of the article is to develop a comprehensive systematization of functional components of the information and institutional environment of corporations, developing an author’s classification of global corporate institutions in the information sphere. Also, investigation of the interaction of completely different institutes in the format of a unified system methodology is considered in the article. Methodology of research. The theoretical and methodological basis of the research are the fundamental positions of modern economic theory and innovative development of business entities, scientific works of scientists, normative and legislative acts of Ukraine and the world on the formation of information and institutional environment of corporations. The following methods are used in the process of research: theoretical generalization (for coverage of theoretical and methodological foundations of the information and institutional environment of corporations activity), induction, deduction (for studying the peculiarities of the formation of the information and institutional environment of corporations activity), system approach (with the purpose of developing the classification of global corporate institutions in the information sphere), graphic (for the purpose of visual representation). Findings. The evolution of the information and institutional environment of corporations activity is considered, the functional components of the information and institutional environment are systematized. The interaction of completely different institutes in the format of a unified system methodology is explored. It is proved that the Bretton Woods institutions are the basic system of rules, which in turn are determined by the national interests of the United States, Great Britain, Germany, Belgium and other European countries. It has been determined that some of the newest corporations are taking on the role of creating rules that by their nature are global in nature and do not depend on the will of national governments and international organizations. Originality. The classification of global corporate institutions in the information sphere has been developed, which contributes to the development of orientation and adaptability to the latest international rules of entrepreneurial activity. Practical value. The obtained results of the study will enable corporations to develop benchmarks and adapt to the latest international rules of business, which will be the driving force for reducing transaction costs. The introduction of a scientific classification of such a classification will enable national corporations and other forms of business to more accurately redistribute resources and orient themselves in the system of business rules at the international level. Key words: institutionalization, institutional transformation, corporation, international institute, development, regulation, informational and institutional environment.